GESTURAL CYBERTEXTUAL CONTEXTS AS BACKGROUND OF SPEECH INTENTIONS ON DIGITAL MEDIA - Rahardi, R Kunjana; Rahmat, Wahyudi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to explore gestural multimodality, which includes hand signals, facial expressions, and body postures, within the context of cybertext. It examines how multimodal, gestural-based communication alters meaning in social media environments. This research is qualitative in nature and utilizes a content analysis approach. The data is sourced from social media text, which is classified and analyzed contextually. The research instruments include data collection through observation and text analysis of multimodal elements. Data analysis is conducted using a multimodal pragmatics approach to evaluate the role of gestural context in online communication. The results of this study identify five roles of gestural context in cybertext: (1) the utilization of gestural context as a basis for individual meaning-making, (2) the implementation of gestural context as a foundation for collective assumptions, (3) the incorporation of gestural context to highlight significance, (4) the integration of gestural context for verification purposes, and (5) the inclusion of gestural context to serve as a means of validation in digital communication.